Peningkatan Hasil Belajar Tolak Peluru Melalui Metode Jigsaw Pada Peserta Didik Kelas VII A Mts Al-Hikmah Klitih Kecamatan Plandaan Kabupaten Jombang Tahun Pelajaran 2014/2015 - Agus Subata (Bravo's : Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2013)
is divided into three parts: the prefix movement, movement execution and final movement. Methods of data collection in this study using the test performance / practice. The instrument used was a test instrument.    Based on this research, the study of students using the jigsaw method showed an increase. ie in the first cycle, showed an average increase of 73.61 niai with klaksikal completeness of 56.25% .and increase learning outcomes of students in the second cycle increased to an average of 90.97 with 100% completeness klaksikal. Keywords: jigsaw Methods, Results Learning.